Cultural Research on Drug Users in Indonesia - Siahaan, BJP Roy Hardi (Universitas Syiah Kuala, 2024)
This study aims to examine the construction of rehabilitation for drug users in Indonesia from various aspects using a literature review approach. The aspects discussed include rehabilitation policies, the role of family and community, societal stigma, as well as cultural perspectives such as identity, consumer culture, and regulatory frameworks. Additionally, this research employs Jurgen Habermas's theory of Communicative Power as its theoretical foundation. The method used is a literature review by examining various previous studies relevant to the topic of drug user rehabilitation. The results indicate that rehabilitation is constructed from policy aspects that still need improvement, the importance of family support, the need to eliminate societal stigma, the diverse identities of drug users, consumer culture related to residence and occupation, and regulatory frameworks encompassing societal regulations and values. The theory of Communicative Power highlights the importance of public space as a deliberative arena in the rehabilitation process involving drug users, families, communities, and other stakeholders. This research provides a comprehensive overview of the construction of drug user rehabilitation in Indonesia from various perspectives and aspects that need attention to enhance the effectiveness of rehabilitation programs.